2008
DOI: 10.1177/0146167207313731
|View full text |Cite
|
Sign up to set email alerts
|

Culture and Context: East Asian American and European American Differences in P3 Event-Related Potentials and Self-Construal

Abstract: Research has demonstrated differences in social and cognitive processes between East Asians and European Americans. Whereas East Asians have been characterized as being more sensitive to situational context and attending more to the perceptual field, European Americans have been characterized as being more focused on the object and being more field independent. The goal of the present experiment was to investigate differences in neural responses to target objects and stimulus context between East Asian America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 51 publications
4
63
1
1
Order By: Relevance
“…Recent work by D. Park and colleagues (Goh et al 2007;Jenkins et al 2009) have amassed evidence from their imaging work that goes beyond the Hedden et al (2008) finding by providing initial evidence for the specific neural pathways of holistic perception. Lewis et al (2008) used an ERP oddball paradigm and investigated the idea that relative to European Americans, Asian Americans pay more attention to contextual stimuli and, as a consequence, they should be more ÒsurprisedÓ when presented with a novel stimulus.…”
Section: Gene X Culture Interaction?mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by D. Park and colleagues (Goh et al 2007;Jenkins et al 2009) have amassed evidence from their imaging work that goes beyond the Hedden et al (2008) finding by providing initial evidence for the specific neural pathways of holistic perception. Lewis et al (2008) used an ERP oddball paradigm and investigated the idea that relative to European Americans, Asian Americans pay more attention to contextual stimuli and, as a consequence, they should be more ÒsurprisedÓ when presented with a novel stimulus.…”
Section: Gene X Culture Interaction?mentioning
confidence: 99%
“…One classic effect in social psychology involves choice. Early on, Lewin (1952) investigated effects of choices (or ÒdecisionsÓ in LewinÕs terminology) on behavioral change and behavioral persistence. Later, choice was at the center of cognitive dissonance research (Festinger 1957).…”
mentioning
confidence: 99%
“…The P1 is a positive deflection peaking roughly 100 ms after stimulus onset on the occipital scalp surface, larger for attended than unattended information. Surprisingly, studies directly comparing two groups of observers did not reveal differences on this component (Goto et al 2010;Lewis et al 2008). For example, Goto et al (2010) manipulated the semantic incongruity between objects and scenes.…”
Section: Introductionmentioning
confidence: 95%
“…If these East vs. West differences are based on individualism vs. collectivism, or on how people from these cultures are context influenced (Lewis et al 2008;Nisbett 2004), then it could be that some Western cultures show an Eastern style of reasoning. We examine whether this is the case for Italians because Italians might be more collectivistic than US Americans (the standard Western culture examined in previous research) and because Italians have been found to more context influenced (when communicating) than US Americans (Rösch and Segler 1987).…”
Section: Intercultural Differences In Reasoning Stylesmentioning
confidence: 99%